Blue marble health : an innovative plan to fight diseases of the poor amid wealth - Hotez, Peter J. (Baltimore : Johns Hopkins University Press, 2016)
In 2011, Dr. Peter J. Hotez relocated to Houston to launch Baylor's National School of Tropical Medicine. He was shocked to discover that a number of neglected diseases often associated with developing countries were widespread in impoverished Texas communities. Despite the United States' economic prowess and first-world status, an estimated 12 million Americans living at the poverty level currently suffer from at least one neglected tropical disease, or NTD. Hotez concluded that the world's neglected diseases-which include tuberculosis, hookworm infection, lymphatic filariasis, Chagas disease, and leishmaniasis-are born first and foremost of extreme poverty. In this book, Hotez describes a new global paradigm known as "blue marble health," through which he asserts that poor people living in wealthy countries account for most of the world's poverty-related illness. By crafting public policy and relying on global partnerships to control or eliminate some of the world's worst poverty-related illnesses, Hotez believes, it is possible to eliminate life-threatening disease while at the same time creating unprecedented opportunities for science and diplomacy
A changing landscape in global health -- The "other diseases": the neglected tropical diseases -- Introducing blue marble health (BMH) -- East Asia : China, Indonesia, Japan, and South Korea -- India -- Sub-Saharan Africa : Nigeria and South Africa -- Middle East and North Africa : ISIS-occupied zones and Saudi Arabia -- In the Americas : Argentina, Brazil, and Mexico -- Australia, Canada, European Union, Russian Federation, and Turkey -- United States of America -- The G20 : "a theory of justice" -- A framework for science and vaccine diplomacy -- Future directions
Includes bibliographical references and index
WorldShare provided record
Keywords: Poor -- Health and hygiene; Tropical medicine -- Economical aspects; World health -- Economic aspects; Neglected Diseases -- economics; Poverty Areas; Global Health -- economics; Health Equity -- economics; Tropical Medicine -- economics; Print books